Immunogenicity of inactivated rotavirus in rhesus monkey, and assessment of immunologic mechanisms. Issue 1 (31st December 2023) - Zhou, Yan; Wu, Jinyuan; Hu, Xiaoqing; Chen, Rong; Lin, Xiaochen; Yin, Na; Lu, Chenxing; Ye, Jun; Zhao, Yongmei; Song, Xiaopeng; Song, Zexin; Wang, Jinlan; et al.
ABSTRACT: Rotavirus is one of the main pathogens causing severe diarrhea in infants and young children < 5 years of age. The development of the next-generation rotavirus vaccine is of great significance for preventing rotavirus infection and reducing severe mortality. The current study aimed to develop and evaluate the immunogenicity of inactivated rotavirus vaccine (IRV) in rhesus monkeys. Monkeys received two or three IRV injections intramuscularly at a 4-week interval. Neutralizing antibodies, cellular immunity, PBMC gene expression profiling, and immune persistence were evaluated. Three-dose immunization of IRV induced a higher level of neutralizing, IgG and IgA antibodies compared to two-dose immunization. IRV induced IFN-γ secretion to mediate cellular immune responses, including robust pro-inflammatory and antiviral responses. Chemokine-mediated signaling pathways and immune response were broadly activated by IRV injection. The IRV-induced neutralizing antibodies resulting from two doses returned to baseline levels 20 weeks after full immunization, while those resulting from three doses returned to baseline levels 44 weeks after full immunization. Increasing immunization dose and injection number will help to improve IRV immunogenicity and neutralizing antibody persistence.